Neural correlates of individual differences in affective benefit of real-life urban green space exposure - Tost, Heike; Reichert, Markus; Braun, Urs; Reinhard, Iris; Peters, Robin; Lautenbach, Sven; Hoell, Andreas; Schwarz, Emanuel; Ebner-Priemer, Ulrich; Zipf, Alexander; Meyer-Lindenberg, Andreas (Nature neuroscience, 2019)
Tost et al. show that urban green space exposure improves well-being, particularly in people dwelling in relatively deprived areas and showing less prefrontal activity during emotion processing, a neural signature that is linked to mental health risk.
Gesehen am 01.04.2020